(untitled) (Heritage, 2024)
The key task of crisis management is to prevent or mitigate the negative consequences of a crisis, whether it concerts organizations or other entities. In crisis management, the most important element is communication.The goal of communication in a crisis situation is to provide information to interested parties, an to protect and maintain the image and reputation of the organization. Given thet the importance of communication for effective crisis management has long been recognized both theory and I practice. The subject of this paper is to evaluate and analyze the effectiveness of social media as a channel of communication in crisis situations.